Processability of A6061 Aluminum Alloy Using Laser Powder Bed Fusion by In Situ Synthesis of Grain Refiners - Michele Rosito; Matteo Vanzetti; Elisa Padovano; Flavia Gili; Roberta Sampieri; Federica Bondioli; Claudio Francesco Badini (Metals, 2023)
Despite the increasing interest in laser powder bed fusion (LPBF), only a few cast aluminum alloys are available for this process. This study focuses on improving the LPBF processability of the A6061 alloy, which is challenging due to its wide solidification range, the dendritic columnar grain growth, and consequent solidification cracking. To address these issues, in situ-synthesized grain refiners can be used to induce equiaxial grain growth and prevent crack formation. A6061 RAM2 powder—a mixture of A6061, Ti, and B4C—was characterized and processed using a low-power LPBF machine to create an in situ particle-reinforced metal matrix composite. Parameter optimization was performed to evaluate the effect of their variation on the printability of the alloy. Microstructural characterization of the samples revealed that the complete reaction and the synthesis of the ceramic reinforcement did not occur. However, TiAl3 was synthesized during the process and promoted a partial grain refinement, leading to the formation of equiaxial grains and preventing the formation of solidification cracks. The tensile tests carried out on the optimized samples exhibit superior mechanical properties compared to those of A6061 processed through LPBF.